2015
DOI: 10.1002/2014ja020583
|View full text |Cite
|
Sign up to set email alerts
|

A full‐wave model for a binary gas thermosphere: Effects of thermal conductivity and viscosity

Abstract: The thermosphere is diffusively separated and behaves as a multiconstituent gas wherein individual species in static equilibrium are each stratified according to their individual scale heights. Gravity waves propagating in the thermosphere cause individual gases to oscillate with different amplitudes and phases. We use a two-gas (N 2 and O) full-wave model to examine the roles of thermal conductivity, viscosity, and mutual diffusion on the wave-induced characteristics of both gases. In the lower thermosphere, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Since there are relatively few observations or modeling studies of this region, comparisons of this amplitude with other work are scarce. Our perturbations are somewhat smaller than those used by Hickey et al () and in line with the relative perturbations found by Chen et al () Becker and Vadas () for the 90–110 km altitude ranges.…”
Section: Methodssupporting
confidence: 92%
“…Since there are relatively few observations or modeling studies of this region, comparisons of this amplitude with other work are scarce. Our perturbations are somewhat smaller than those used by Hickey et al () and in line with the relative perturbations found by Chen et al () Becker and Vadas () for the 90–110 km altitude ranges.…”
Section: Methodssupporting
confidence: 92%
“…Additionally, dissipation altitudes predicted by these preliminary simulations agree with the results reported here and are consistent with the upper bound reported in Smith et al [] that the waves dissipate by 400 km. These preliminary simulations are also consistent with predictions of the spectral full‐wave model of H09, which models effects due to variable atmospheric composition with the inclusion of a vertically varying mean molecular weight obtained from the Mass Spectrometer Incoherent Scatter (MSIS) model [ Hedin , ] and has been employed to explicitly examine the one‐gas approximation in the context of wave‐induced changes in composition [ Walterscheid and Hickey , ] and the implications of a binary gas thermosphere on viscosity and thermal conductivity [ Hickey et al ., ], which found that those effects become significant only above ~250 km.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers compared TEC results with the state-of-the-art Embry-Riddle Aeronautical University (ERAU) model [Snively, 2013;Heale and Snively, 2015;Zettergren and Snively, 2015;Hickey et al, 2015], and they found a good agreement between the ERAU model and acoustic-wave-generated TEC perturbations.…”
Section: 1002/2015rs005910mentioning
confidence: 99%